Aplicação do método WTF para estimativa da recarga do aquífero livre da região da bacia do Rio Gramame e do baixo curso do Rio Paraíba/PB - Fernandes, Lucila Araújo (2017)
The main objective of this work is to estimate the free aquifer recharges of the Gramame river basin and the Baixo Paraíba river basin, located in the Northeast region of Brazil, using the Water Table Fluctuation - WTF method. This study area was defined within the scope of an international research and cooperation project, the BRAMAR project (Strategies and Technologies for Mitigation of the Water Scarcity in Northeast Brazil). The application of this method is simple and requires the static level variation data (?h) and the specific yield value of the aquifer (Sy). The recharge was estimated for 2016; however, the monitoring step started in October 2015. The monitoring process was carried out manually and sensors that measure the water level in a time step of 15 minutes were installed in some wells. The monitored wells are tubular and “cacimbão”, which are shallow wells of 1.70 m average diameter. A total of 39 wells were monitored, of which 20 are large diameter wells and 19 are tubular. The specific yield coefficient, as well as other hydrodynamic parameters of the aquifer, were determined by pumping tests. The pumping test data of the tubular wells were analyzed using the software AQTESOLV Demo, and the pumping test data of the large diameter wells were analyzed using the Papadopulos & Cooper method. The results obtained from the pumping tests showed storage coefficient – S values – ranging from 0.04 to 0.13. The transmissivity – T values – ranged from 8,53x10-6 m2/s and 9.51x10-4 m2/s. The annual direct recharge in the wells ranged between 41.33 mm and 426.47 mm, with an average of 184.88 mm for the studied area, representing 11.70% of the average precipitation, which was 1,579.73 mm. Maintenance of the static level monitoring is recommended, as well as a deeper analysis of the hydrodynamic parameters of the aquifer, in order to subsidize the sustainable management of groundwater resources in the region.